In vitro permeation of palladium powders through intact and damaged human skin. (1st May 2018) - Crosera, Matteo; Mauro, Marcella; Bovenzi, Massimo; Adami, Gianpiero; Baracchini, Elena; Maina, Giovanni; Larese Filon, Francesca
Highlights: We tested in vitro Pd powders permeation trough intact and damaged human skin. The effect of an early decontamination with a common cleanser was assessed too. After 24 h exposure Pd solution permeates both skin types. Damaged skin protocol enhances Pd permeation. Intact skin early decontamination reduces both Pd penetration and permeation. Abstract: The use of palladium (Pd) has grown in the last decades, commonly used in automotive catalytic converters, jewellery and dental restorations sectors. Both general and working population can be exposed to this metal, which may act as skin sensitizer. This study investigated in vitro palladium powders permeation through excised intact and damaged human skin using the Franz diffusion cell method and the effect of rapid skin decontamination using sodium laureth-sulphate. 1 mL of a 10 min sonicated suspension made of 2.5 g of Pd powder in 50 mL synthetic sweat at pH 4.5 and room temperature was applied to the outer surface of the skin membranes for 24 h. Pd permeation, assessed by ICP-MS, was higher when damaged skin was used (p = 0.03). Final flux permeation values and lag times were 0.02 ± 0.01 μg cm −2  h −1 and 6.00 ± 3.95 h for intact, and 0.10 ± 0.02 μg cm −2  h −1 and 2.05 ± 1.49 h for damaged skin samples, respectively. Damaged skin protocol enhances Pd skin penetration inside dermal layer (p = 0.04), thus making the metal available for systemic uptake. Pd penetration (p = 0.02) and permeation (p = 0.012) through intact skin decreased significantly when a cleaning procedure was applied. This study demonstrates that after skin exposure to Pd powders a small permeation of the metal happen both through intact and damaged skin and that an early decontamination with a common cleanser can significantly decrease the final amount of metal available forsystemic uptake.